Mentoring practice as a condition of continuous business education - A. A. Kanke (Вестник университета)
The article presents a descriptive study of the mentoring practice in business education. The approaches, needs and problems of mentoring in the field of entrepreneurship as a factor of socio-economic development of the country are considered. The article focuses on graduates of MBA programs who have a high level of acquired knowledge, good education and experience, occupy fairly high positions or run their own business. In addition, it was noted that entrepreneurial mentoring should be implemented and built through a formal and organized process. At the same time, the achievement of sustainable development goals and initiatives in all spheres of life depends on the effective mentoring of people who play a two-way role, contributing to personal development, skills, talents, experience and education for the development of other individuals, as well as for society as a whole. It is concluded that mentoring offers a potentially transformative impact on the career orientation of business education programs graduates’, positively affects the opportunities for opening, formation and development of business sustainability. The study suggests options for finding a mentor for an MBA graduate in terms of public initiatives, participation in accelerators or special projects and programs, the use of paid mentoring resources, as well as the development of their own mentoring programs based on a business school. The author concludes that the proposed options will allow mentee to more confidently manage business processes and ensure the development of the company, thereby increasing their professional value.